Optimal temperature for growth and feed conversion of immature cod (Gadus morhua L.) - Björnsson, Björn; Steinarsson, Agnar; Oddgeirsson, Matthías (ICES Journal of Marine Science, 2001)
Five size groups of hatchery reared cod (2–109 g) and three size groups of wild cod (447–2213 g) were reared at a range of constant temperatures. All groups were fed to satiation, the hatchery fish on dry feed and the wild fish on capelin and shrimp. The optimal temperature for growth decreased linearly with fish weight on a log scale from 17°C for 2 g fish to 7°C for 2000 g fish. Similarly, the optimal temperature for feed conversion decreased with fish weight, from 15°C for 2 g fish to 7°C for 2000 g fish. Growth rate at optimal temperature declined linearly with fish weight on a log–log scale from 5.8 to 0.36% per day for 2 and 2000 g cod, respectively.